Building back fairer from the Covid-19 pandemic in South Africa: Some first step reforms in an era of fiscal constraints - Arndt, Channing; Davies, Robert J.; Gabriel, Sherwin; Harris, Laurence; Sachs, Michael; van Seventer, Dirk Ernst (International Food Policy Research Institute, 2021)
Prior to the onset of the COVID-19 pandemic, South Africa confronted an unfolding economic crisis. Today, the economic situation has worsened in essentially every dimension. If there is a silver lining to this terrible pandemic from the perspective of the South African economy, it could be found in an enhanced willingness to implement reform measures designed to rekindle growth, improve equity, and drive sustainable development whilst recognizing significant fiscal constraints. To this end, this paper focuses on three areas: skills; food systems, nutrition, and health; and urban structure. In each area, we first briefly consider long run perspectives and then turn attention to high return positive steps that can be implemented in the very near term and are consistent with the realization of a positive long run vision. We find that much greater openness to immigration of highly skilled and experienced workers (and their families) stands out as a rapidly implementable that offers strong potential to stimulate growth, create jobs, and reduce inequality at low costs to government and with low risk. With respect to food systems, nutrition, and health, we point to a solid basis for optimism about growth and employment prospects in the long term. We also highlight the potential benefits of holistic perspectives that include implications for nutrition and health. Turning to the very near term, we underline the need to reduce the uncertainty associated with land reform. In this optic, we recommend consideration of a focus of reform in the near term on favorable dryland areas that can be equipped with supplemental irrigation, with the goal of permitting these areas to specialize in higher value products. Judicious water resource use planning must accompany this policy. Turning to urban structure, we the persistence of the spatial inequities entrenched by the apartheid era. With tight fiscal constraints on government investment that are likely to extend to the medium term, we seek to refocus on measures designed to increase efficiency and equity outcomes derived from existing infrastructure. The analyses of these three areas complement the growth agenda released by the National Treasury in August 2019 and the discussions contained in a series of papers published by Economic Research South Africa (ERSA) over 2021.